ANALISIS PENGARUH MANAJEMEN LABA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2012) - Dimas Prasetia; Marsono Marsono (Diponegoro Journal of Accounting, 2015)
This study aims to examine the influence of earnings management to corporate social responsibility report with corporate governance as moderating variable. The role of corporate governance is required to minimize the influence of earnings management to corporate social responsibility report. In this study, earnings management is measured by using modified jones model, and corporate social responsibility report is measured by GRI Index. Proxies used to measure corporate governance are managerial ownership, institutional ownership, the number of audit committee, board size, and the number of board meetings. This study use secondary data with population of manufactured companies listed in Indonesia stock exchange in 2010-2012. The method used to determine the sample is purposive sampling. The analytical method used is multiple regression. The result of this study shows that earnings management has significant influence to corporate social responsibility report. The result of the test for moderating variables show that managerial ownership and board size have significant effect where managerial ownership has negative effect and board size has positive effect.